2007
DOI: 10.1016/j.healun.2007.07.028
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Right Ventricular Endomyocardial Biopsy for the Diagnosis of Xenograft Rejection After CD46 Pig-to-Baboon Cardiac Transplantation

Abstract: Introduction-Endomyocardial biopsy (EmBx) is the standard means of establishing cardiac allograft rejection diagnosis. The efficacy of this procedure in xenotransplantation has not been determined. In this study we compare the histology of right ventricular EmBx specimens with the corresponding full cross sections of explanted right ventricle (RV). We also compare RV with the related left ventricle (LV) cross sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…More aggressive salvage therapies may also include B-cell and plasma cell depletion and complement inhibition [ 105 , 106 ]. In CXTx, there are few studies which have attempted to diagnose and treat presumptive rejection episodes, most of these after hCXTx [ 9 , 25 , 33 , 107 109 ]. Putative rejection episodes were diagnosed based on biochemical markers (troponin T, AST), graft contractility, telemetric measures of cardiac performance, and echocardiography.…”
Section: Diagnosis and Treatment Of Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…More aggressive salvage therapies may also include B-cell and plasma cell depletion and complement inhibition [ 105 , 106 ]. In CXTx, there are few studies which have attempted to diagnose and treat presumptive rejection episodes, most of these after hCXTx [ 9 , 25 , 33 , 107 109 ]. Putative rejection episodes were diagnosed based on biochemical markers (troponin T, AST), graft contractility, telemetric measures of cardiac performance, and echocardiography.…”
Section: Diagnosis and Treatment Of Rejectionmentioning
confidence: 99%
“…Putative rejection episodes were diagnosed based on biochemical markers (troponin T, AST), graft contractility, telemetric measures of cardiac performance, and echocardiography. Serial biopsies after oCXTx will likely be applicable for diagnosis of rejection [ 109 111 ], but the difficulty of obtaining endomyocardial biopsies in NHPs has limited their exploration in animal models. When presumptive rejection episodes were treated using steroids, or steroids and ATG, there was no evidence for reversal of rejection, and, unsurprisingly, in some instances, excessive antirejection therapy increased the frequency of infectious complications [ 9 , 25 ].…”
Section: Diagnosis and Treatment Of Rejectionmentioning
confidence: 99%
“…Ricci et al [43] explored the value of right ventricular endomyocardial biopsy for the diagnosis of rejection after pig-to-baboon heterotopic cardiac xenoTx. Their results indicated that delayed xenograft rejection is a widespread process involving both right and left ventricles similarly.…”
Section: Cell Transplantation As a Form Of Xenotransplantationmentioning
confidence: 99%
“…Ricci et al. analyzed the histopathology of CD46‐transgenic pig hearts transplanted into baboons for the diagnosis of xenograft rejection [6]. They showed that linear regression analysis of histology scores from endomyocardial biopsies and cross sections of explanted hearts equally represented histology of right and left ventricle tissue.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Authors concluded that delayed xenograft rejection was a widespread process involving similarly both right and left ventricles. Histological assessment of the right ventricle by endomyocardial biopsy could therefore be an effective method for monitoring xenograft rejection after cardiac xenotransplantation [6].…”
Section: Preclinical Studiesmentioning
confidence: 99%